Pengembangan Bahan Ajar Digital Berbasis Web Pada Materi Mitigasi Bencana Alam - Nurdin, Iqbal; Sumarmi; Sahrina , Alfi; Bachri, Syamsul (Geography Education Study Program, Universitas Kanjuruhan Malang, 2025)
Based on needs analysis, as many as 75% of students have difficulty understanding the material presented by the teacher. Disaster mitigation learning in class still uses printed teaching materials which do not help students' understanding. The use of printed teaching materials and boring learning does not fully support the learning process. The aim of this research is to produce website-based digital teaching materials using identification of website addresses with the domain classgeografi.com and to test the suitability of teaching materials for the learning process. The research method uses the ADDIE model with five development stages, namely: Analysis, Design, Development, Implementation and Evaluation. Data collection was carried out based on the results of validation carried out by material and media validators and analyzed using quantitative and qualitative descriptive analysis. Feasibility test of digital teaching materials by material validators (83%) and media validators (96%) with the feasibility category